Influenza prevalence and vaccine efficacy among diabetic patients in Qatar. Issue 5 (May 2023) - Thomas, Swapna; Emara, Mohamed M.; Ouhtit, Allal; Nader, Joanne D.; Nasrallah, Gheyath K.; Coyle, Peter V.; Althani, Asmaa A.; Al Maslamani, Muna A.; Yassine, Hadi M.
Abstract: Seasonal influenza viruses may lead to severe illness and mortality in patients with comorbidities, including Diabetes Mellitus (DM). Vaccination against influenza in DM patients may reduce influenza incidence and severity. Before the emergence of the COVID-19 pandemic, influenza infections were the most prevalent respiratory infections in Qatar. Still, reports about influenza prevalence and vaccine efficacy in DM patients have not been reported. This study aimed to analyze influenza prevalence among other respiratory infections and assess influenza vaccine efficacy in DM patients in Qatar. Statistical analysis was performed on data obtained from Hamad Medical Corporation (HMC) database for patients that visited the emergency department (ED) with respiratory-like illnesses. The analysis was done for the period between January 2016 to December 2018. Among 17, 525 patients who visited HMC-ED with clinical symptoms of respiratory infections, 2611(14.9%) were reported to have DM. Among DM patients, influenza was the most prevalent respiratory pathogen at 48.9%. Influenza virus A (IVA) was the most circulating type, contributing to 38.4%, followed by IVB contributing to 10.4% of total respiratory infections. Among the typed IVA-positive cases, 33.4% were H1N1, and 7.7% were H3N2. A significant decrease in influenza infections was reported in vaccinated DM patients (14.5%) when compared to non-vaccinated patients (18.9%) (p-value = 0.006). However, there was no significant relaxation in the clinical symptoms among vaccinated DM patients compared to their non-vaccinated counterparts. In conclusion, influenza was the most common etiology for respiratory viral infection among diabetic patients at the leading healthcare provider in Qatar. Although vaccination reduced the incidence rate among DM patients, it was less effective in preventing symptoms. Further studies on a larger cohort and for a more extended period are required to investigate influenza prevalence and vaccine efficacy among DM patients.